Leaf morphological traits of nine major tropical trees of Shorea species (Dipterocarpaceae) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mufarhatun N, Susilowati A, Hilwan I, Arrofaha N, Yulita KS, Dwiyanti FG, Hidayat A, Kamiya K, Rachmat HH. 2023. Leaf morphological traits of nine major tropical trees of Shorea species (Dipterocarpaceae). Biodiversitas 24: 1704-1712. Shorea is the largest genus in the Dipterocarpaceae family and has high leaf morphological variations among its species, which causes difficulties in field identification. Therefore, information on the specific characteristics of the leaf morphology of each species is needed. This study aimed to examine and discriminate leaf morphological traits at both mature and sapling stages of nine Shorea species, namely Shorea balangeran (Korth.) Burck, S. leprosula Miq., S. mecistopteryx Ridl., S. multiflora (Burck) Symington, S. ovalis (Korth.) Blume, S. pinanga Scheff., S. platyclados Slooten ex Endert, S. selanica (Wight & Arn.) Blume, and S. stenoptera Burck. The leaves of 90 mature trees growing in the Dramaga Research Forest (DRF) and Gunung Dahu Research Forest (GDRF) as well as the leaves of 180 saplings growing in the nursery of Forest Research and Development Center (FRDC) were observed. Leaf traits, leaf color, and chlorophyll content were assessed on 3 leaves from each mature tree and 5 from each sapling collected. Furthermore, comparative analysis using F independent test in the one-way analysis variance (ANOVA), multivariate analysis using Principal Component Analysis (PCA), and Hierarchical Cluster Analysis were used in this study. The results showed that 8 of the 11 measured morphological traits were identified as the quantitative leaves morphological differentiators, namely Leaves Width (LW), Lamina Length (LL), the length between the largest Leaves Point (LP) with the base of the leaves, angle of leaves vein (SD), Petiole Length (PL), number of leaves vein (LB), breadth of the leaves (WL), and the Circumference of the Leaves (CL). In addition, the results of cluster analysis showed the nine Shorea spp. are clustered into two major groups. Group 1 consisted of species, S. stenoptera, and S. mecistopteryx, while the remaining are included in Group 2. Our findings conclude that the eight leaf morphological traits obtained from this study are useful as additional characters to distinguish the nine Shorea species in the field.